Anti-reflection film

By forming an anti-fouling layer on the low refractive index layer of the anti-fouling film, combined with the ionizing radiation curable composition and the technical means of surface treatment of alumina particles, the anti-fouling film is solved when frequent finger contact and solvent wipes are frequently encountered. and the problem of insufficient abrasion resistance, high abrasion resistance, stain resistance and wear durability are achieved.

CN119452277APending Publication Date: 2025-02-14HIGASHIYAMA FILM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380050731.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-13
Filing Date
2023-12-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When existing anti-reflective films frequently contact with fingers and wipe with alcohol and other solvents, they are difficult to meet the anti-fouling and scratch resistance, and there are wear problems.

Method used

An anti-reflective film with a hard coating layer and a low refractive index layer formed on the substrate film. The low refractive index layer is composed of an ionizing radiation curable composition, including a (meth)acrylate compound with reactive groups and hollow di Silicon oxide particles and surface-treated alumina particles and a stain-resistant layer is formed on the surface of the composition containing fluorine (meth)acrylate.

Benefits of technology

The anti-reflective film has excellent abrasion resistance, antifouling properties and wear durability, and can withstand friction of cloth or fingers with solvents such as alcohol attached.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119452277A_ABST
    Figure CN119452277A_ABST
Patent Text Reader

Abstract

Provided is an antireflection film having excellent scratch resistance, high antifouling properties and wear durability, and solvent resistance capable of withstanding friction by a finger or a cloth to which a solvent such as an alcohol adheres. An antireflection film (10) is provided with a base film (12), a hard coat layer (14) formed on the surface of the base film (12), and a low-refractive-index layer (16) formed on the surface of the hard coat layer (14), and the low-refractive-index layer (16) is configured from a cured product of an ionizing radiation-curable composition. The ionizing radiation curable composition contains a (meth) acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth) acrylate compound. The surface of the antireflection film has a water contact angle of 100 DEG or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an antireflection film, and more particularly to an antireflection film suitable for use on a display surface such as a liquid crystal display, an organic EL display, a touch panel of a smartphone, etc. Background Art

[0002] In order to prevent external light from being reflected into the screen, etc., an anti-reflection film is sometimes configured on the display surface of the touch panel of a liquid crystal display, an organic EL display, a smart phone, etc. As an anti-reflection film, it is known that an anti-reflection film has a hard coat layer and an anti-reflection layer (low refractive index layer) in order on a substrate film. For example, in patent document 1 applied by the applicant, by studying the composition of the low refractive index layer formed on the surface of the hard coat layer, the anti-reflection property, scratch resistance, and antifouling property of the anti-reflection film are improved. In patent document 1, a fluorine-containing compound is contained in the low refractive index layer, which contributes to the improvement of antifouling property.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2021 / 020504 Summary of the invention

[0006] Problem that the invention aims to solve

[0007] In anti-reflection films, especially anti-reflection films that are frequently touched by fingers, such as those configured on the surface of a touch panel, it is required to have high antifouling properties. As disclosed in Patent Document 1, by adding a substance with antifouling effect represented by a fluorine-containing compound in the low refractive index layer constituting the anti-reflection film, the antifouling property of the anti-reflection film can be improved. On the other hand, an antifouling layer containing these substances with antifouling effects is also used as a layer independent of the low refractive index layer. However, even if an antifouling layer is provided, there is a situation where sufficiently high antifouling properties cannot be obtained or the surface is worn and the antifouling properties decrease when the contact of the finger is repeated. In anti-reflection films that are frequently touched by fingers, in addition to having high antireflection properties and antifouling properties, from the perspective of durability during use, having high scratch resistance and having high wear durability also become important characteristics.

[0008] In addition, in recent years, in particular, in the case of anti-reflection films that are frequently touched by fingers, such as anti-reflection films disposed on the surface of touch panels, the use of solvents such as alcohol to wipe the surface for cleaning or sterilization has increased. However, conventional anti-reflection films have the following problems: when wiped with a cloth with alcohol attached or repeatedly operated with fingers with alcohol attached, the surface of the anti-reflection film may be worn or the antifouling property may be reduced.

[0009] The problem to be solved by the present invention is to provide an antireflection film having excellent scratch resistance, high antifouling property and wear durability, and having solvent resistance that can withstand friction with a cloth or fingers with a solvent such as alcohol attached thereto.

[0010] Solutions for solving problems

[0011] In order to solve the above-mentioned problems, the antireflection film according to the present invention has the following structure.

[0012] [1] The first antireflection film according to the present invention is an antireflection film comprising a substrate film, a hard coating layer formed on a surface of the substrate film, and a low refractive index layer formed on a surface of the hard coating layer, wherein the low refractive index layer is composed of a cured product of an ionizing radiation curable composition, wherein the ionizing radiation curable composition contains a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, and wherein the water contact angle of the surface of the antireflection film is 100° or more.

[0013] [2] In the embodiment of [1] above, the ionizing radiation curable composition constituting the low refractive index layer may further contain a fluorine-containing (meth)acrylate.

[0014] [3] The second antireflection film according to the present invention is an antireflection film comprising a substrate film, a hard coating layer formed on a surface of the substrate film, a low refractive index layer formed on a surface of the hard coating layer, and an antifouling layer formed on a surface of the low refractive index layer, wherein the low refractive index layer is composed of a cured product of an ionizing radiation curable composition, the ionizing radiation curable composition containing a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, the antifouling layer is composed of a cured product of an ionizing radiation curable composition containing a fluorine-containing (meth)acrylate, and the water contact angle of the surface of the antireflection film is 100° or more.

[0015] [4] In the above aspect [3], the content of the fluorine-containing (meth)acrylate in the antifouling layer may be 90% by mass or more based on the total solid content of the antifouling layer.

[0016] [5] In the above-mentioned embodiment [3] or [4], the low refractive index layer may not contain a fluorine-containing compound.

[0017] Effects of the Invention

[0018] The first antireflection film of the present invention having the structure of [1] is an antireflection film having a substrate film, a hard coating layer formed on the surface of the substrate film, and a low refractive index layer formed on the surface of the hard coating layer, wherein the low refractive index layer is composed of a cured product of an ionizing radiation curable composition, the ionizing radiation curable composition containing a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, and the surface of the antireflection film has a water contact angle of 100° or more. Since the low refractive index layer is composed of a cured product of a composition containing, in addition to the (meth)acrylate compound, alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, the antireflection film has excellent scratch resistance and high antifouling properties and wear durability. Furthermore, since the surface water contact angle of the antireflection film having such a composition is 100° or more, the antireflection film has high antifouling properties and has solvent resistance that allows it to withstand friction with a cloth or fingers with a solvent such as alcohol attached thereto.

[0019] In the above aspect [2], since the ionizing radiation curable composition constituting the low refractive index layer further contains a fluorine-containing (meth)acrylate, the antifouling property and solvent resistance of the surface of the antireflection film can be effectively improved.

[0020] The second antireflection film of the present invention having the structure of [3] is an antireflection film having a substrate film, a hard coating layer formed on the surface of the substrate film, a low refractive index layer formed on the surface of the hard coating layer, and an antifouling layer formed on the surface of the low refractive index layer, wherein the low refractive index layer is composed of a cured product of an ionizing radiation curable composition, the ionizing radiation curable composition contains a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, the antifouling layer is composed of a cured product of an ionizing radiation curable composition containing a fluorine-containing (meth)acrylate, and the water contact angle of the surface of the antireflection film is 100° or more. Since the low refractive index layer is composed of a cured product of a composition containing aluminum oxide particles surface-treated by a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound in addition to the (meth)acrylate compound, and the antifouling layer composed of a cured product of a composition containing a fluorine-containing (meth)acrylate is provided on the low refractive index surface, the antireflection film has excellent scratch resistance and high antifouling properties and wear durability. In addition, since the water contact angle of the surface of the antireflection film is 100° or more, the antireflection film has high antifouling properties and has solvent resistance that can withstand friction by a cloth or a finger with a solvent such as alcohol attached.

[0021] In the above aspect [4], since the content of the fluorine-containing (meth)acrylate in the antifouling layer is 90% by mass or more based on the total solid content of the antifouling layer, the antifouling property of the antireflection film can be effectively improved.

[0022] In the above-mentioned aspect [5], since the low refractive index layer does not contain a fluorine-containing compound, the scratch resistance of the antireflection film can be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a cross-sectional view of the antireflection film according to the first embodiment of the present invention.

[0024] Figure 2 It is a cross-sectional view of an antireflection film according to a second embodiment of the present invention.

[0025] Figure 3 It is a cross-sectional view of an antireflection film according to a third embodiment of the present invention.

[0026] Figure 4 It is a cross-sectional view of an antireflection film according to a fourth embodiment of the present invention.

[0027] Figure 5 It is a cross-sectional view of an antireflection film according to a fifth embodiment of the present invention. DETAILED DESCRIPTION

[0028] The present invention is described in detail below. In this specification, various physical properties refer to values ​​at room temperature and in the atmosphere unless otherwise specified. In addition, in this specification, the refractive index of a substance or a material layer refers to the refractive index at a measurement wavelength of 589.3 nm unless otherwise specified.

[0029] <Anti-reflection film according to first embodiment>

[0030] Figure 1 1 is a cross-sectional view of an antireflection film according to a first embodiment of the present invention. Figure 1 As shown, the anti-reflection film 10 according to the first embodiment of the present invention comprises: a base film 12; a hard coating layer 14 formed on the surface of the base film 12; and a low refractive index layer 16 formed on the surface of the hard coating layer 14. In this embodiment, the above-mentioned layers are stacked in sequence without any other layers therebetween. The low refractive index layer 16 becomes a layer exposed on the outermost surface of the anti-reflection film 10 as a whole.

[0031] (Base film)

[0032] The substrate film 12 is not particularly limited as long as it has transparency. As the substrate film 12, transparent polymer films, glass films, etc. can be listed. Transparency refers to a total light transmittance of 50% or more in the visible light wavelength region, and the total light transmittance is more preferably 85% or more. The above-mentioned total light transmittance can be measured in accordance with JIS K7361-1 (1997). The thickness of the substrate film 12 is not particularly limited, but from the viewpoint of excellent operability, it is preferably in the range of 2 μm or more and 500 μm or less. More preferably, it is in the range of 2 μm or more and 200 μm or less. In addition, "film" generally refers to a film having a thickness of less than 0.25 mm, but if the thickness is more than 0.25 mm and can be rolled into a roll, even if it is a film with a thickness of more than 0.25 mm, it is also included in the "film".

[0033] As the polymer material of the substrate film 12, polyester resins such as polyethylene terephthalate resin and polyethylene naphthalate resin, polycarbonate resin, poly (meth) acrylate resin, polystyrene resin, polyamide resin, polyimide resin, polyacrylonitrile resin, polypropylene resin, polyethylene resin, polycycloolefin resin, cycloolefin copolymer resin and other polyolefin resins, triacetyl cellulose resin, diacetyl cellulose resin and other cellulose resins, polyphenylene sulfide resin, polyvinyl chloride resin, polyvinylidene chloride resin, polyvinyl alcohol resin, etc. can be listed. The polymer material of the substrate film 12 can be composed of only one of them, or it can be composed of a combination of more than two kinds. Among them, from the viewpoints of optical properties or durability, polyethylene terephthalate resin, polyimide resin, polycarbonate resin, poly (meth) acrylate resin, polycycloolefin resin, cycloolefin copolymer resin, triacetyl cellulose resin is more preferred.

[0034] The substrate film 12 may be composed of a single layer including a layer containing one or more of the above-mentioned polymer materials, or may be composed of two or more layers including a layer containing one or more of the above-mentioned polymer materials and a layer containing one or more polymer materials different from the layer.

[0035] (Hard Coating)

[0036] The hard coating layer 14 helps to improve the scratch resistance of the anti-reflection film 10. The hard coating layer 14 is composed of a cured product of an ionizing radiation curable composition containing a (meth) acrylate compound having a reactive group. Ionizing radiation refers to an electromagnetic wave or charged particle beam having an energy quantum that can polymerize or crosslink molecules among electromagnetic waves or charged particle beams. As ionizing radiation, electromagnetic waves such as ultraviolet rays (UV), X-rays, and gamma rays, charged particle beams such as electron beams (EB), alpha rays, and ion beams can be listed. Among them, ultraviolet rays (UV) are particularly preferred from the perspective of productivity. Hereinafter, the ionizing radiation curable composition is sometimes referred to as a curable composition. In addition, in this specification, "(meth) acrylate" refers to "at least one of acrylate and methacrylate". "(Meth) acryl" refers to "at least one of acryloyl and methacryloyl". "(Meth) acrylic acid" refers to "at least one of acrylic acid and methacrylic acid". "(Meth) acrylic acid" refers to "at least one of acrylic acid and methacrylic acid". "(Meth) acrylic acid compound" is a compound having a (meth) acrylic acid group, and monomers, oligomers, prepolymers, etc. can be listed. Hereinafter, the (meth)acrylate compound may be simply referred to as (meth)acrylate.

[0037] The (meth)acrylate may be a monofunctional (meth)acrylate or a multifunctional (meth)acrylate. Alternatively, it may be a combination of a monofunctional (meth)acrylate and a multifunctional (meth)acrylate. From the viewpoint of improving curability, the curable composition more preferably contains a multifunctional (meth)acrylate as the (meth)acrylate.

[0038] As (meth) acrylate, carbamate (meth) acrylate, silicone (meth) acrylate, (meth) alkyl acrylate, (meth) aryl acrylate, etc. can be listed. Among them, carbamate (meth) acrylate is preferred, and carbamate (meth) acrylate oligomer is particularly preferred. As a specific example of carbamate (meth) acrylate, for example, a substance obtained by reacting a polyisocyanate compound, a hydroxyl-containing (meth) acrylate compound, and a polyol compound as required can be listed. As a polyisocyanate compound, for example, diisocyanate compounds such as hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, xylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and their urate modified bodies, adduct modified bodies, biuret modified bodies, etc. can be listed. As a hydroxyl-containing (meth) acrylate compound, for example, hydroxyethyl (meth) acrylate, hydroxypropyl (meth) acrylate, trimethylolpropane diacrylate, pentaerythritol tri (meth) acrylate, dipentaerythritol penta (meth) acrylate and their polyoxyalkylene (Polyoxyalkylene) modified bodies, polylactone modified bodies, etc. can be listed. As a polyol compound, for example, ethylene glycol, propylene glycol, butanediol, hexaglycol, polyoxyethylene glycol, polyoxypropylene glycol, glycerol, trimethylolpropane, pentaerythritol, biphenol, bisphenol, etc. can be listed. In the case where the curable composition for forming the hard coating 14 includes carbamate (meth) acrylate as an ultraviolet curable resin, since the hard coating 14 has moderate softness, the bending resistance of the anti-reflection film 10 becomes high, and it can be suitably used for flexible displays that are repeatedly bent such as foldable displays or rollable displays. Furthermore, even if the base film 12 is made of polycycloolefin or cycloolefin copolymer, which is relatively easy to break, the breakage of the base film 12 can be easily suppressed.

[0039] As the (meth)acrylate constituting the curable composition, it is preferred to further contain a pentaerythritol (meth)acrylate compound. As specific examples of the pentaerythritol (meth)acrylate compound, pentaerythritol tri (meth)acrylate, pentaerythritol tetra (meth)acrylate, dipentaerythritol penta (meth)acrylate, dipentaerythritol hexa (meth)acrylate, tripentaerythritol tetra (meth)acrylate, tripentaerythritol penta (meth)acrylate, tripentaerythritol hexa (meth)acrylate, tripentaerythritol hepta (meth)acrylate, tripentaerythritol octa (meth)acrylate, etc. can be cited. It is particularly preferred to contain pentaerythritol tri (meth)acrylate in the curable composition.

[0040] In the curable composition forming the hard coat 14, in addition to including the ultraviolet curable resin, non-ultraviolet curable resin may also be included, but it may not be included. In addition, in the curable composition forming the hard coat 14, a photopolymerization initiator may also be included. In addition, as required, additives that can be usually added to the curable composition may also be included. As additives, dispersants, leveling agents, defoamers, thixotropic agents, antifouling agents, antibacterial agents, flame retardants, slip agents, antistatic agents, inorganic particles, resin particles, etc. may be listed. In addition, as required, a solvent may also be included.

[0041] As non-ultraviolet curable resins, thermoplastic resins, thermosetting resins, etc. can be listed. As thermoplastic resins, polyester resins, polyether resins, polyolefin resins, polyamide resins, etc. can be listed. As thermosetting resins, unsaturated polyester resins, epoxy resins, alkyd resins, phenolic resins, etc. can be listed.

[0042] Examples of the photopolymerization initiator include alkylphenone-based, acylphosphine oxide-based, and oxime ester-based photopolymerization initiators. Examples of the alkylphenone-based photopolymerization initiator include 2,2'-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1 -ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, 2-benzylmethyl-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-(4-morpholinophenyl)-1-butanone, 2-(4-methylbenzyl)-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone, N,N-dimethylaminoacetophenone, etc. Examples of the acylphosphine oxide-based photopolymerization initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide. Examples of the oxime ester photopolymerization initiator include 1,2-octanedione, 1-[4-(phenylthio)phenyl]-2-(O-benzoyloxime), ethyl ketone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-1-(O-acetyloxime), etc. The photopolymerization initiator may be used alone or in combination of two or more.

[0043] The content of the photopolymerization initiator is preferably in the range of 0.1% by mass or more and 10% by mass, and more preferably 1% by mass or more and 5% by mass or less, based on the total solid content of the curable composition.

[0044] Inorganic particles and resin particles can be added to the hard coating layer 14 for purposes such as preventing the hard coating layer 14 from sticking or adjusting the refractive index of the hard coating layer 14. By forming minute surface irregularities on the hard coating layer 14 with the added inorganic particles or resin particles, it is easy to suppress sticking of the front and back surfaces when the hard coating film including the base film 12 and the hard coating layer 14 is rolled into a roll before forming the low refractive index layer 16.

[0045] As inorganic particles capable of adjusting the refractive index of the hard coating layer 14, metal oxide particles including oxides of metals such as titanium, zirconium, tin, zinc, silicon, niobium, aluminum, chromium, magnesium, germanium, gallium, antimony, and platinum can be listed. As inorganic particles capable of optical adjustment, one of them can be used alone, or two or more can be used in combination. Among them, titanium oxide and zirconium oxide are particularly preferred from the viewpoints of high refractive index and excellent transparency. In addition, as resin particles, for example, resin particles including resins such as (meth) acrylic resin, styrene resin, styrene-(meth) acrylic resin, urethane resin, polyamide resin, silicone resin, epoxy resin, phenolic resin, polyethylene resin, and cellulose can be listed. As resin particles, one of them can be used alone, or two or more can be used in combination.

[0046] The thickness of the hard coating layer 14 is not particularly limited, but is preferably 0.5 μm or more from the viewpoint of having sufficient hardness, etc. More preferably, it is 0.75 μm or more. In addition, from the viewpoint of easily suppressing curling caused by the difference in thermal shrinkage with the base film 12, it is preferably 20 μm or less. More preferably, it is 10 μm or less. The thickness of the hard coating layer 14 refers to the thickness of a relatively smooth portion of a portion without unevenness caused by inorganic particles or resin particles in the thickness direction.

[0047] The refractive index of the hard coat layer 14 is preferably within a range of 1.49 to 1.56 from the viewpoint of suppressing interference unevenness caused by a difference in refractive index between the base film 12 and the hard coat layer 14 .

[0048] From the viewpoint of preventing blocking, etc., the arithmetic mean roughness Ra of the surface having surface irregularities of the hard coat layer 14 is preferably within a range of 0.3 nm to 20 nm, and more preferably 0.5 nm to 10 nm.

[0049] As the solvent used in the curable composition for forming the hard coating layer 14, there can be listed: alcohol solvents such as ethanol, isopropyl alcohol (IPA), n-butyl alcohol (NBA), ethylene glycol monomethyl ether (EGM), ethylene glycol monoisopropyl ether (IPG), propylene glycol monomethyl ether (PGM), diethylene glycol monobutyl ether, etc.; ketone solvents such as methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclohexanone, acetone, etc.; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate (EtAc), propyl acetate, isopropyl acetate, butyl acetate (BuAc), etc.; amide solvents such as N-methylpyrrolidone, acetamide, dimethylformamide, etc. As the solvent, one of them can be used alone, or two or more of them can be used in combination.

[0050] The solid content concentration (concentration of components other than the solvent) of the curable composition may be appropriately determined in consideration of coating properties, film thickness, etc. For example, it may be 1% by mass to 90% by mass, 1.5% by mass to 80% by mass, 2% by mass to 70% by mass, etc.

[0051] (Low refractive index layer)

[0052] In the antireflection film 10 according to the present embodiment, a low refractive index layer 16 is provided as an antireflection layer on the surface of the hard coat layer 14. The low refractive index layer 16 has a lower refractive index than the hard coat layer 14 and exhibits an antireflection effect due to the difference in refractive index with the hard coat layer 14.

[0053] The low refractive index layer 16 is composed of a cured product of an ionizing radiation curable composition containing a (meth) acrylate compound with a reactive group as a binder resin, a surface-treated aluminum oxide particle by a silane coupling agent having a reactive group that can form a bond with the (meth) acrylate compound, and hollow silica particles. As described above with respect to the hard coat 14, the ionizing radiation includes various electromagnetic waves and charged particle beams, but the low refractive index layer 16 is preferably composed of a cured product of an ultraviolet (UV) curable composition. In addition, the reactive groups contained in the (meth) acrylate compound and the silane coupling agent are preferably ultraviolet reactive. Below, the suitable composition of the composition is described.

[0054] Examples of the (meth)acrylate compound having a reactive group include urethane (meth)acrylate, silicone (meth)acrylate, alkyl (meth)acrylate, aryl (meth)acrylate, etc. The (meth)acrylate compound may have only a (meth)acryloyl group as a reactive group, or may have another reactive group in addition to the (meth)acryloyl group.

[0055] The (meth)acrylate may consist of only a monofunctional (meth)acrylate, only a polyfunctional (meth)acrylate, or a combination of a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate. As the (meth)acrylate, it is more preferable to contain a polyfunctional (meth)acrylate.

[0056] Examples of the monofunctional (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, amyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, , nonyl (meth) acrylate, decyl (meth) acrylate, isodecyl (meth) acrylate, undecyl (meth) acrylate, dodecyl (meth) acrylate, lauryl (meth) acrylate, stearyl (meth) acrylate, isostearyl (meth) acrylate, isobornyl (meth) acrylate, 1-adamantyl (meth) acrylate, 2-methyl-2-adamantyl (meth) acrylate, 2-ethyl-2-adamantyl (meth) acrylate, bornyl (meth) acrylate, tricyclodecyl (meth) acrylate, dimethicone Cyclopentyl (meth)acrylate, dicyclopentenyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, 1-naphthylmethyl (meth)acrylate, 2-naphthylmethyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxy-2-methylethyl (meth)acrylate, phenoxyethoxyethyl (meth)acrylate, 3-phenoxy-2-hydroxypropyl (meth)acrylate, 2-phenylphenoxyethyl (meth)acrylate, 4-phenylphenoxyethyl (meth)acrylate, 3-(2-phenylphenyl) ...3-(2-phenylphenyl)-2-hydroxypropyl (meth)acrylate, 3- )-2-hydroxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, butoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, methoxyethylene glycol (meth)acrylate, ethoxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, and the like.

[0057] Examples of the polyfunctional (meth)acrylate include difunctional (meth)acrylate, trifunctional (meth)acrylate, and tetrafunctional (meth)acrylate. More specifically, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol tetra(meth)acrylate, tripentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, tripentaerythritol octa(meth)acrylate, etc. can be mentioned.

[0058] The (meth)acrylate compound contained in the curable composition may be composed of one of the above-mentioned (meth)acrylates alone, or may be composed of two or more. From the viewpoint of improving scratch resistance, the (meth)acrylate compound contained in the curable composition preferably contains a polyfunctional (meth)acrylate having five or more functionalities, and it is preferred to increase the content of the polyfunctional (meth)acrylate having five or more functionalities.

[0059] In addition, it is preferred that the multifunctional (meth)acrylate contains a dimer. The dimer of the multifunctional (meth)acrylate can easily improve the curing rate of the curable composition due to its excellent curing speed, and thus can further improve the scratch resistance. Among them, it is preferred to include at least one selected from the group of dimers including pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate and dipentaerythritol hexa(meth)acrylate, and more preferably include at least one selected from the group of dimers including pentaerythritol triacrylate, dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate.

[0060] From the viewpoint of scratch resistance, transparency, and solubility in solvents, the content of the dimer is preferably in the range of 25% by mass or more and 50% by mass or less based on the total solid content of the multifunctional (meth)acrylate, and more preferably 30% by mass or more and 40% by mass or less.

[0061] Moreover, the curable composition constituting the low refractive index layer 16 preferably contains a fluorine-containing (meth) acrylate as a part of the (meth) acrylate compound having a reactive group. In this way, it is possible to impart high antifouling properties to the anti-reflection film 10. As specific examples of fluorine-containing (meth) acrylates, (meth) acrylates containing perfluoropolyether groups and the like can be cited. A perfluoropolyether group refers to a group in which all hydrogen in a polyether such as polyethylene glycol or polypropylene glycol is replaced by fluorine. For example, a fluorine polyether group having a repeating structure formed by any one of perfluoromethylene oxide, (-CF2O-), perfluoroethylene oxide (-CF2CF2O-), perfluoropropylene oxide (-CF2CF2CF2O-), perfluoroisopropylene oxide (-CF(CF3)CF2O-) or a combination of multiple thereof can be cited. The number of repeating units of the above-mentioned repeating structure is preferably 1 to 100. Specific examples of the compound include "KY-1203", "KY-1207", "KY-1211", "KY-1216", and "KY-1240" manufactured by Shin-Etsu Chemical, "MEGAFAC RS-75" manufactured by DIC, "OPTOOL DAC-HP" and "OPTOOL DAC-100" manufactured by Daikin Industries, and "FTERGENT 601AD" and "FTERGENT 601ADH2" manufactured by Neos. Such fluorinated (meth)acrylates can suppress the adhesion of dirt or fingerprints, and can also easily remove dirt or fingerprints.

[0062] The fluorine-containing (meth)acrylate preferably has no urethane bond in its structure. By making the fluorine-containing (meth)acrylate have no urethane bond in its structure, the hardness of the low refractive index layer 16 becomes high, and the low refractive index layer 16 has particularly high wear durability.

[0063] The content of fluorinated (meth) acrylate in the low refractive index layer 16 is preferably 1.0% by mass or more and 15.0% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 16. When the content of fluorinated (meth) acrylate in the low refractive index layer 16 is 1.0% by mass or more relative to 100% by mass of the solid content of the low refractive index layer 16, the smoothness of the surface of the low refractive index layer 16 is improved, and the scratch resistance is improved. In addition, the antifouling property is improved. And, from this viewpoint, the content of fluorinated (meth) acrylate in the low refractive index layer 16 is more preferably 3.0% by mass or more relative to 100% by mass of the solid content of the low refractive index layer 16, and more preferably 5.0% by mass or more. And, when the content of fluorinated (meth) acrylate in the low refractive index layer 16 is 15.0% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 16, the decline of scratch resistance is suppressed. In addition, from this viewpoint, the content of the fluorine-containing (meth) acrylate in the low refractive index layer 16 is more preferably 13.0% by mass or less, and further preferably 10.0% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 16. In addition, the solid content of the low refractive index layer 16 mentioned here refers to the components excluding the components that are liquid at room temperature and are not fixed to the binder resin in the low refractive index layer 16. As the solid content of the low refractive index layer 16, aluminum oxide particles, hollow silica particles, and a binder resin are included. It does not include an oil component as an additive or a surfactant that is not fixed to the binder resin.

[0064] By including aluminum oxide particles in the low refractive index layer 16, convex portions are formed on the surface of the low refractive index layer 16. By forming convex portions on the surface of the low refractive index layer 16 with aluminum oxide particles, the low refractive index layer 16 can have good scratch resistance.

[0065] Alumina particles can be solid particles or hollow particles, but alumina particles are preferably solid particles. Solid particles refer to particles that do not substantially have cavities inside the particles, and are particles in which the proportion of cavities is less than 5% of the volume of solid particles. Hollow particles refer to particles that have cavities inside the particles, and are particles in which the proportion of cavities is more than 5% of the volume of hollow particles. When the alumina particles are solid particles, the scratch resistance of the low refractive index layer 16 is improved, and the scratch resistance of the anti-reflection film 10 is improved. On the other hand, when the alumina particles are hollow particles, the refractive index of the refractive index layer 16 can be reduced, and the reflection of light can be reduced. In hollow particles, the proportion of cavities is preferably more than 10% and less than 80% of the volume of the hollow particles. When the proportion of cavities is more than 10%, the refractive index can be reduced and the reflection of light can be reduced. It is more preferably more than 20%, and more preferably more than 30%. On the other hand, when the proportion of cavities is less than 80%, the decline in the dispersibility of alumina particles can be suppressed. It is more preferably less than 60%.

[0066] The shape of the alumina particles is not particularly limited, and may be spherical, needle-shaped, scaly, rod-shaped, fibrous, amorphous, etc. Among them, spherical is preferred.

[0067] The aluminum oxide particles are surface-treated with a silane coupling agent having a reactive group capable of forming a bond with a (meth)acrylate compound. By providing the silane coupling agent with a reactive group capable of forming a bond with a (meth)acrylate compound, the aluminum oxide particles surface-treated with the silane coupling agent can be firmly bonded to the (meth)acrylate contained in the low refractive index layer 16, and can also be bonded to the reactive group contained in the adjacent resin layer such as the hard coating layer 14. When these bonds are formed, the wear durability and solvent resistance of the anti-reflection film 10 are improved.

[0068] Silane coupling agents are usually bonded to silicon atoms in the molecule and have hydrolyzable groups and functional groups other than these. Here, the hydrolyzable group refers to a substituent that is directly bonded to the silicon atom and can produce a siloxane bond through a hydrolysis reaction and / or a condensation reaction. As the hydrolyzable group, for example, a halogen atom, an alkoxy group, an acyloxy group, and an alkenyloxy group can be listed. In the case where the hydrolyzable group has a carbon atom, the number of carbon atoms is preferably 6 or less, and more preferably 4 or less. Particularly preferred are alkoxy groups with a carbon number of 4 or less or alkenyloxy groups with a carbon number of 4 or less. The hydrolyzable group is hydrolyzed to form a bond with the oxygen atoms on the surface of the aluminum oxide particles, so that the aluminum oxide particles are surface treated.

[0069] The silane coupling agent used here contains, in addition to the above-mentioned hydrolyzable group, a reactive group that can form a bond with a (meth)acrylate compound. As the reactive group, carbon-carbon unsaturated double bond groups such as (meth)acryloyl, vinyl, styryl, and allyl, ring-opening polymerizable groups such as epoxy, and oxetanyl groups can be listed. These reactive groups are ultraviolet reactive. In the low refractive index layer 16 containing a (meth)acrylate compound having a reactive group and aluminum oxide particles surface-treated by a silane coupling agent having a reactive group, the reactive group of the (meth)acrylate compound reacts with the reactive group of the silane coupling agent to form a bond.

[0070] Examples of the silane coupling agent having a carbon-carbon unsaturated double bond group as a reactive group include p-phenylvinyltrimethoxysilane, 2-(allyloxymethyl)acrylate (trimethoxysilyl)propyl, 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, p-phenylvinyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, and 7-octenyltrimethoxysilane.

[0071] Examples of the silane coupling agent having a ring-opening polymerizable group as a reactive group include 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 8-glycidoxyoctyltrimethoxysilane.

[0072] Among them, from the viewpoint of reactivity with (meth)acrylate compounds, silane coupling agents having a carbon-carbon unsaturated double bond group are preferably used, and among them, silane coupling agents having an ethylenic carbon-carbon double bond group such as a (meth)acryloyl group, a vinyl group, a styryl group, and an allyl group are particularly preferred.

[0073] The content of the silane coupling agent is preferably set to a range of 1 part by mass or more and 50 parts by mass or less relative to 100 parts by mass of the alumina particles. In this way, the effect of the surface treatment performed by the silane coupling agent is improved. In addition, the scratch resistance of the low refractive index layer 16 can be maintained at a high level, and the wear durability and solvent resistance can be improved. More preferably, its content is 10 parts by mass or more and 40 parts by mass or less. In the low refractive index layer 16, silane coupling agents that are not bonded to the alumina particles may also remain, and the preferred content range described here refers to the content of the silane coupling agent as a whole, including these silane coupling agents that are not bonded to the alumina particles.

[0074] In order to form convex portions on the surface of the low refractive index layer 16 and obtain good scratch resistance, the difference (rd) between the average particle size r of the aluminum oxide particles and the thickness d of the low refractive index layer 16 can be 10 nm or more. The difference (rd) is more preferably 15 nm or more, and more preferably 18 nm or more. On the other hand, from the viewpoint of suppressing the height of the convex portion formed and maintaining transparency, the difference (rd) is 300 nm or less. It is more preferably 200 nm or less, and more preferably 100 nm or less.

[0075] The average particle size r of the aluminum oxide particles is preferably within a range of 60 nm or more and 400 nm or less, although it also depends on the thickness d of the low refractive index layer 16. It is more preferably 70 nm or more, and further preferably 90 nm or more. In addition, it is more preferably 300 nm or less, and further preferably 200 nm or less. The average particle size r of the aluminum oxide particles is an arithmetic mean value based on volume obtained by a laser diffraction / scattering method in accordance with JIS Z8825, and includes not only a primary particle size but also a secondary particle size as an agglomerate of particles.

[0076] The content of the aluminum oxide particles in the low refractive index layer 16 can be 0.1% by mass or more and 6.0% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 16. When the content of the aluminum oxide particles in the low refractive index layer 16 is 0.1% by mass or more relative to 100% by mass of the solid content of the low refractive index layer 16, excellent scratch resistance can be obtained. In addition, from this viewpoint, the content of the aluminum oxide particles in the low refractive index layer 16 is more preferably 1.0% by mass or more relative to 100% by mass of the solid content of the low refractive index layer 16, and more preferably 2.0% by mass or more. And, when the content of the aluminum oxide particles in the low refractive index layer 16 is 6.0% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 16, high transparency can be obtained. In addition, from this viewpoint, the content of the aluminum oxide particles in the low refractive index layer 16 is more preferably 5.5% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 16, and more preferably 5.0% by mass or less.

[0077] Hollow silica particles are particles whose average particle diameter is smaller than the average thickness d of the low refractive index layer 16. Hollow silica particles can be particles whose average particle diameter is smaller than that of alumina particles forming convex portions on the surface of the low refractive index layer 16. Hollow silica particles are particles whose surface convexities do not substantially contribute to the formation of the low refractive index layer 16. Hollow silica particles refer to particles having cavities inside the particles, and are particles whose proportion of cavities is more than 5% of the volume. Hollow refers to a shell structure composed of an outer shell and a cavity inside it, or a porous structure having many cavities, etc. Since the hollow silica particles are hollow structures, the refractive index of the low refractive index layer 16 can be lowered, and the reflection of light can be reduced. The shape of the hollow silica particles is not particularly limited, but preferably spherical, spindle-shaped, egg-shaped, flat, cubic, amorphous, etc. Among them, spherical, flat, cubic, etc. are particularly preferred.

[0078] In the hollow silica particles, the proportion of the cavity is preferably 10% or more and 80% or less by volume. When the proportion of the cavity is 10% or more by volume, the refractive index can be lowered and the reflection of light can be reduced. It is more preferably 20% or more by volume, and further preferably 30% or more by volume. On the other hand, when the proportion of the cavity is 80% or less by volume, the decrease in the dispersibility of the hollow silica particles can be suppressed. It is more preferably 60% or less by volume.

[0079] The average particle size of hollow silica particles is preferably more than 5nm and less than 100nm, although it also depends on the thickness d of low refractive index layer 16. More preferably more than 20nm, more preferably more than 40nm. In addition, more preferably less than 80nm, more preferably less than 70nm. When the average particle size of hollow silica particles is within these preferred ranges, excellent anti-reflection effect and transparency can be obtained in low refractive index layer 16. The average particle size is the arithmetic mean value based on volume obtained by following the laser diffraction / scattering method of JIS Z8825. Not only a primary particle size is included, but also a secondary particle size as an agglomerate of particles.

[0080] The refractive index of the hollow silica particles is preferably in the range of 1.01 to 1.45. It is more preferably in the range of 1.15 to 1.38, and further preferably in the range of 1.15 to 1.35. When the refractive index of the hollow silica particles is within this range, an excellent anti-reflection effect can be obtained.

[0081] The content of the hollow silica particles in the low refractive index layer 16 can be 6.0% by mass or more and 49.9% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 16. When the content of the hollow silica particles in the low refractive index layer 16 is 6.0% by mass or more relative to 100% by mass of the solid content of the low refractive index layer 16, excellent anti-reflection properties can be obtained. In addition, from this viewpoint, the content of the hollow silica particles in the low refractive index layer 16 is more preferably 10% by mass or more relative to 100% by mass of the solid content of the low refractive index layer 16, more preferably 20% by mass or more, and particularly preferably 30% by mass or more. In addition, when the content of the hollow silica particles in the low refractive index layer 16 is 49.9% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 16, the decrease in scratch resistance is suppressed. From this viewpoint, the content of the hollow silica particles in the low refractive index layer 16 is more preferably 45% by mass or less, and further preferably 40% by mass or less, based on 100% by mass of the solid content of the low refractive index layer 16 .

[0082] Furthermore, the total amount of the aluminum oxide particles and the hollow silica particles in the low refractive index layer 16 can be 10% by mass or more and 50% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 16. When the total amount of the aluminum oxide particles and the hollow silica particles in the low refractive index layer 16 is 10% by mass or more relative to 100% by mass of the solid content of the low refractive index layer 16, excellent scratch resistance can be obtained. In addition, from this viewpoint, the total amount of the aluminum oxide particles and the hollow silica particles in the low refractive index layer 16 is more preferably 20% by mass or more relative to 100% by mass of the solid content of the low refractive index layer 16, and further preferably 30% by mass or more. On the other hand, when the total amount of the aluminum oxide particles and the hollow silica particles in the low refractive index layer 16 is 50% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 16, the aluminum oxide particles and the hollow silica particles can be sufficiently maintained in the low refractive index layer 16, so excellent scratch resistance can be obtained. From this viewpoint, the total amount of the alumina particles and the hollow silica particles in the low refractive index layer 16 is more preferably 45% by mass or less, and even more preferably 40% by mass or less, based on 100% by mass of the solid content of the low refractive index layer 16 .

[0083] The low refractive index layer 16 is formed by using an ionizing radiation curable composition comprising a (meth)acrylate compound having a reactive group, aluminum oxide particles surface-treated by a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound, and hollow silica particles. In the low refractive index layer 16, after irradiation with ionizing radiation, bonds are formed via reactive groups between (meth)acrylate compounds, between aluminum oxide particles subjected to surface treatment, between (meth)acrylate compounds and aluminum oxide particles subjected to surface treatment, or between these (meth)acrylate compounds or aluminum oxide particles subjected to surface treatment and components having reactive groups contained in adjacent layers, so that the low refractive index layer 16 has high scratch resistance, wear durability, and solvent resistance. As described above, the reactive groups contained in the (meth)acrylate compound and the silane coupling agent are preferably ultraviolet reactive. When the (meth)acrylic compound and the aluminum oxide particles have reactive groups that are reactive to ultraviolet rays, by irradiating the low refractive index layer 16 formed by the composition containing the (meth)acrylic compound and the surface-treated aluminum oxide particles with ultraviolet rays, the scratch resistance, wear durability and solvent resistance of the low refractive index layer 16 are improved, and the scratch resistance, wear durability and solvent resistance of the anti-reflection film 10 are improved.

[0084] In addition, the composition for forming the low refractive index layer 16 preferably includes a photopolymerization initiator when the (meth) acrylic compound includes a substance having a reactive group with ultraviolet reactivity (when the (meth) acrylic compound is an ultraviolet curable resin). Moreover, the composition for forming the low refractive index layer 16 may also include a solvent (a solvent used as a dispersion medium in a particle dispersion of aluminum oxide particles, and / or a solvent added separately in addition to the solvent) as required. The binder resin of the low refractive index layer 16 may be composed only of ultraviolet curable resins such as (meth) acrylic resin, or may be composed of a combination of ultraviolet curable resins and non-ultraviolet curable resins. As non-ultraviolet curable resins, photopolymerization initiators, and solvents, the chemical substances listed as specific examples of non-ultraviolet curable resins, photopolymerization initiators, and solvents that can be contained in the composition for forming the hard coat layer 14 can also be appropriately applied in the composition for forming the low refractive index layer 16.

[0085] The content of the photopolymerization initiator is preferably in the range of 0.1% by mass or more and 10% by mass or less based on the total solid content of the composition for forming the low refractive index layer 16. More preferably, it is 1% by mass or more and 5% by mass or less.

[0086] In addition, additives may be included in the low refractive index layer 16 as needed. Examples of such additives include dispersants, leveling agents, defoamers, thixotropic agents, antibacterial agents, flame retardants, lubricants, refractive index adjusters, inorganic particles other than alumina particles, resin particles, etc. In the case of containing inorganic particles other than alumina particles, these inorganic particles may also be surface-treated by a silane coupling agent having a reactive group capable of forming a bond with a (meth)acrylate compound, similarly to the alumina particles.

[0087] In the present embodiment, the surface of the anti-reflection film 10, i.e., the surface of the low refractive index layer 16, has a water contact angle of 100° or more. Thus, the anti-reflection film 10 has high antifouling properties. In addition, the smoothness of the surface of the low refractive index layer 16 is improved, which contributes to the improvement of scratch resistance. From the viewpoint of obtaining higher antifouling properties, the water contact angle of the surface of the low refractive index layer 16 is preferably 105° or more, and more preferably 110° or more. The water contact angle of the surface of the low refractive index layer 16 depends on the component composition of the constituent material of the low refractive index layer 16. For example, by making the low refractive index layer 16 contain fluorine-containing (meth) acrylate or silicone-containing (meth) acrylate, the water contact angle becomes larger. In addition, by giving tiny concavoconvexities to the surface of the low refractive index layer 16, the water contact angle of the surface of the low refractive index layer 16 can also be increased. In the present embodiment, the aluminum oxide particles contained in the low refractive index layer 16 can play this role. However, imparting concavoconvex to the surface of the low refractive index layer 16 may reduce the wiping property of the surface. From the viewpoint of reducing this possibility, it is preferred to replace the method of imparting concavoconvex, or on the basis of this method, use a method of adding fluorine-containing (meth) acrylate or silicone-containing (meth) acrylate to increase the water contact angle. The water contact angle on the surface of the low refractive index layer 16 does not particularly set an upper limit, but is roughly below 130°.

[0088] The refractive index of low refractive index layer 16 is not particularly limited as long as it is lower than hard coating layer 14, but is preferably more than 1.35 and less than 1.52. When the refractive index is more than 1.35, the strength of low refractive index layer 16 can be sufficient, and good scratch resistance can be obtained. On the other hand, when the refractive index is less than 1.52, the anti-reflection film 10 can be made more low reflectivity. From the above viewpoint, the refractive index of low refractive index layer 16 is more preferably more than 1.38 and less than 1.50, and more preferably more than 1.40 and less than 1.49.

[0089] The average thickness d of the low refractive index layer 16 is preferably within a range of 80 nm or more and 110 nm or less. More preferably, it is 85 nm or more, and more preferably, it is 90 nm or more. In addition, it is more preferably 105 nm or less, and more preferably, it is 100 nm or less. When it is within this range, a good low visual reflectivity can be obtained, and the reflection of light can be reduced. The thickness of the low refractive index layer 16 is the thickness of the relatively smooth part in the part without the concave and convex part caused by the aluminum oxide particles in the thickness direction.

[0090] (Method for producing anti-reflection film)

[0091] When manufacturing the anti-reflection film 10, it is sufficient to form a hard coating layer 14 and a low refractive index layer 16 on the surface of the substrate film 12 in order. When forming each layer, the composition for forming each layer is applied, and after drying as required, it is cured by a method corresponding to the curability of the composition, such as irradiation of ionizing radiation represented by ultraviolet rays. After forming a certain layer, the composition for forming the next layer is applied, and after drying as required, the composition is cured. By repeating this process in sequence, a laminated structure of a hard coating layer 14 and a low refractive index layer 16 can be formed to manufacture the anti-reflection film 10.

[0092] In the coating of the composition forming each layer, a wet method can be suitably used. Specifically, for example, various coating methods such as reverse gravure coating, direct gravure coating, die coating, rod coating, wire bar coating, roll coating, spin coating, dip coating, spray coating, knife coating, kiss coating, or various printing methods such as inkjet, offset printing, screen printing, and flexographic printing can be used.

[0093] The drying step for each layer is not particularly limited as long as the solvent used in the coating liquid can be removed, but is preferably performed at a temperature of 50 to 150° C. for about 10 to 180 seconds.

[0094] In the ultraviolet irradiation for each layer, a high pressure mercury lamp, an electrodeless (microwave type) lamp, a xenon lamp, a metal halide lamp, or any other ultraviolet irradiation device can be used. If necessary, ultraviolet irradiation can also be performed under an inert gas atmosphere such as nitrogen. The ultraviolet irradiation amount is not particularly limited, but is preferably 50 to 800 mJ / cm 2 , more preferably 100 to 300 mJ / cm 2 .

[0095] When the hard coating layer 14 is formed on the surface of the substrate film 12, the surface of the substrate film 12 may be subjected to a surface treatment before coating in order to improve the adhesion between the substrate film 12 and the hard coating layer 14. Examples of the surface treatment include corona treatment, plasma treatment, hot air treatment, ozone treatment, and ultraviolet treatment.

[0096] (Properties of anti-reflection film)

[0097] The anti-reflection film 10 of the above structure comprises a substrate film 12, a hard coating layer 14 formed on the surface of the substrate film 12, and a low refractive index layer 16 formed on the surface of the hard coating layer 14, wherein the low refractive index layer 16 is composed of a cured product of an ionizing radiation curable composition, wherein the ionizing radiation curable composition contains a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated by a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound. The water contact angle of the surface of the anti-reflection film 10 is greater than 100°, so that the anti-reflection film 10 has excellent scratch resistance, and has high antifouling properties, wear durability, and solvent resistance.

[0098] In the anti-reflection film 10 involved in the present embodiment, since the water contact angle on the surface is more than 100°, the anti-reflection film 10 has high anti-fouling properties. Since the anti-reflection film 10 has high anti-fouling properties, dirt such as fingerprints is not easy to adhere to the surface of the anti-reflection film 10, and even if it is attached, it can be easily removed. In addition, in the anti-reflection film 10 involved in the present embodiment, the aluminum oxide particles contained in the low refractive index layer 16 contribute to the scratch resistance of the anti-reflection film 10. Moreover, the aluminum oxide particles are surface-treated as described above, and the formation of bonds between the aluminum oxide particles and the (meth) acrylate compound helps to improve the wear durability and solvent resistance. In this way, the anti-reflection film 10 involved in the present embodiment has high anti-reflection and anti-fouling properties, as well as high scratch resistance, wear durability, and solvent resistance, so it is particularly suitable for uses that are frequently touched by fingers, such as the surface configured on the touch panel. Since the antireflection film 10 has high solvent resistance, even when the surface of the antireflection film 10 is rubbed with a cloth or fingers with a solvent such as alcohol for cleaning or sterilization, the surface can maintain high scratch resistance or wear durability.

[0099] From the viewpoint of good visual recognition, the haze of the anti-reflection film 10 is preferably 2.0 or less, more preferably 1.5 or less, and further preferably 1.0 or less. The lower the visual reflectivity of the anti-reflection film 10, the better, and it is more preferably 2.5% or less, and further preferably 2.0% or less. If the visual reflectivity is 2.0% or less, it can be considered that the anti-reflection film 10 has sufficiently high anti-reflection properties.

[0100] From the viewpoint of achieving both scratch resistance and wear durability, the arithmetic mean roughness Ra of the surface of the low refractive index layer 16 is preferably within a range of 1.0 nm to 20 nm, more preferably 3.0 nm to 15 nm, and even more preferably 5.0 nm to 10 nm.

[0101] <Anti-reflection film of the second embodiment>

[0102] Figure 2 2 shows an anti-reflection film 20 according to the second embodiment. The anti-reflection film 20 according to the second embodiment includes: a substrate film 12; a hard coating layer 14 formed on the surface of the substrate film 12; a low refractive index layer 16 formed on the surface of the hard coating layer 14; and an antifouling layer 18 formed on the surface of the low refractive index layer 16.

[0103] The antireflection film 20 according to the second embodiment is different from the antireflection film 10 according to the first embodiment in that it has an antifouling layer 18 on the surface of the low refractive index layer 16. Other than this, it is the same as the antireflection film 10 according to the first embodiment, and the description of the same configuration is omitted.

[0104] (Antifouling layer)

[0105] In the antireflection film 20 according to the present embodiment, the antifouling layer 18 is provided on the surface of the low refractive index layer 16. The antifouling layer 18 improves the antifouling property of the antireflection film 20.

[0106] The antifouling layer 18 is composed of a cured product of an ionizing radiation curable composition containing a fluorine-containing (meth)acrylate, and is preferably composed of a cured product of an ultraviolet curable composition.

[0107] By making the antifouling layer 18 consist of a cured product of a composition containing fluorine-containing (meth)acrylate, the antireflection film 20 having the antifouling layer 18 on the surface has excellent antifouling properties and solvent resistance, and excellent wear durability and scratch resistance. As specific examples of fluorine-containing (meth)acrylate, (meth)acrylate containing perfluoropolyether group and the like can be cited. Perfluoropolyether group refers to a group in which all hydrogen in polyethers such as polyethylene glycol or polypropylene glycol is replaced by fluorine. For example, fluoropolyether group having a repeating structure formed by any one of perfluoromethylene oxide, (-CF2O-), perfluoroethylene oxide (-CF2CF2O-), perfluoropropylene oxide (-CF2CF2CF2O-), perfluoroisopropylene oxide (-CF(CF3)CF2O-) or a combination of multiple thereof can be cited. The number of repeating units of the above-mentioned repeating structure is preferably 1 to 100. Specific examples of the compound include "KY-1203", "KY-1207", "KY-1211", "KY-1216", and "KY-1240" manufactured by Shin-Etsu Chemical Co., Ltd., "MEGAFAC RS-75" manufactured by DIC, "OPTOOL DAC-HP" and "OPTOOL DAC-100" manufactured by Daikin Industries, Ltd., and "FTERGENT 601AD" and "FTERGENT 601ADH2" manufactured by Neos.

[0108] The fluorine-containing (meth)acrylate preferably does not have a urethane bond in its structure. When the fluorine-containing (meth)acrylate does not have a urethane bond in its structure, the hardness of the antifouling layer 18 becomes high, and the antifouling layer 18 can have particularly high wear durability.

[0109] In the antifouling layer 18, the content of fluorine-containing (meth) acrylate is preferably 90% by mass or more based on the total solid content of the antifouling layer 18. As a result, the effect of improving the antifouling property of fluorine-containing (meth) acrylate can be obtained at a higher level. From the viewpoint of further improving the effect of improving the antifouling property, in the antifouling layer 18, the content of fluorine-containing (meth) acrylate is more preferably 92% by mass or more based on the total solid content of the antifouling layer 18. In addition, it is more preferred that the total amount of the resin components constituting the antifouling layer 18 excluding unavoidable components is fluorine-containing (meth) acrylate. In addition, the solid content of the antifouling layer 18 mentioned here refers to the components excluding the components that are liquid at room temperature in the antifouling layer 18 that are not fixed to the curable components. As the solid component of the antifouling layer 18, fluorine-containing (meth) acrylate and the like are included.

[0110] The antifouling layer 18 can be formed using a composition containing a fluorine-containing (meth)acrylate. After the composition for forming the antifouling layer 18 is arranged in a layered manner on the surface of the low refractive index layer 16, it is cured. When the antifouling layer 18 is formed as a cured product of a composition having ultraviolet curability, the composition for forming the antifouling layer 18 preferably further contains a photopolymerization initiator. In addition, a solvent may also be included as needed.

[0111] As the photopolymerization initiator and the solvent, the chemical substances listed as specific examples of the photopolymerization initiator and the solvent that can be contained in the composition for forming the hard coat layer 14 can also be appropriately used in the composition for forming the antifouling layer 18. The content of the photopolymerization initiator is preferably set in the range of 0.1 mass % or more and 15 mass % or less based on the total solid content of the composition for forming the antifouling layer 18. It is more preferably 3 mass % or more and 10 mass % or less.

[0112] In addition, the antifouling layer 18 may also contain additives as needed. As such additives, antifouling agents other than fluorine-containing (meth)acrylates, dispersants, leveling agents, defoaming agents, thixotropic agents, antibacterial agents, flame retardants, slip agents, refractive index adjusters, etc. can be listed. However, from the viewpoint of improving the smoothness of the surface of the antifouling layer 18, the antifouling layer 18 preferably does not contain solid particles represented by metal oxide particles such as alumina particles or hollow silica particles. Even if the antifouling layer 18 contains solid particles, it is sufficient to suppress the particle size of the solid particles to less than 10nm, and suppress the content of the solid particles to less than 1% by mass relative to 100% by mass of the solid content of the antifouling layer 18.

[0113] In the present embodiment, the water contact angle of the surface of the anti-reflection film 20, i.e., the surface of the anti-fouling layer 18, is greater than 100°. Thus, the anti-reflection film 20 has high anti-fouling properties. In addition, since the smoothness of the surface of the anti-fouling layer 18 is improved, it helps to improve the scratch resistance. From the viewpoint of obtaining higher anti-fouling properties, the water contact angle of the surface of the anti-fouling layer 18 is preferably greater than 105°, and more preferably greater than 110°. For example, by increasing the content of fluorine-containing (meth)acrylate in the anti-fouling layer 18, the water contact angle of the surface of the anti-fouling layer 18 becomes larger. There is no particular upper limit for the water contact angle of the surface of the anti-fouling layer 18, but it is approximately less than 130°.

[0114] The thickness of the antifouling layer 18 is preferably 1 nm or more. In this case, the antifouling layer 18 can achieve a higher effect of improving the antifouling property. More preferably, the thickness of the antifouling layer 18 is 3 nm or more, and further can be 5 nm or more. On the other hand, the thickness of the antifouling layer 18 is preferably 15 nm or less. In this case, the antireflection property of the antireflection film 20 can be ensured to be high. More preferably, the thickness of the antifouling layer 18 can be 10 nm or less.

[0115] The refractive index of the antifouling layer 18 is preferably 1.6 or less. If it is 1.6 or less, the antireflection property of the antireflection film 20 can be highly ensured. More preferably, the refractive index of the antifouling layer 18 is 1.55 or less, and further can be 1.50 or less. On the other hand, the refractive index of the antifouling layer 18 is not particularly limited as long as the thickness of the antifouling layer 18 is within the above range, and is preferably 1.3 or more, and more preferably 1.35 or more.

[0116] From the viewpoint of achieving both scratch resistance and wear durability, the arithmetic mean roughness Ra of the surface of the antifouling layer 18 is preferably within a range of 1.0 nm to 20 nm, more preferably 3.0 nm to 15 nm, and even more preferably 5.0 nm to 10 nm.

[0117] In the anti-reflection film 20 involved in this embodiment, the composition of the low refractive index layer 16 can be the same as the composition in the anti-reflection film 10 involved in the first embodiment, but unlike the anti-reflection film 10 involved in the first embodiment, an antifouling layer 18 is provided on the low refractive index layer 16. The antifouling layer 18 exerts high antifouling properties, so it is not necessary to make the low refractive index layer 16 contain a fluorine-containing compound for the purpose of improving antifouling properties. When the low refractive index layer 16 contains a large amount of fluorine-containing compounds, the wettability with the composition for forming the antifouling layer 18 becomes low, and the adhesion with the antifouling layer 18 is weakened, resulting in a decrease in the scratch resistance of the antireflection film 20. By not containing the fluorine-containing compound in the low refractive index layer 16, the scratch resistance of the antireflection film 20 can be improved. Even when the low refractive index layer 16 contains a fluorine-containing compound, it is only necessary to suppress its content to 1% by mass or less relative to 100% by mass of the solid content of the low refractive index layer 16.

[0118] In the anti-reflection film 20 involved in this embodiment, the antifouling layer 18 is provided in direct contact with the surface of the low refractive index layer 16. For example, a primer layer having an adhesion-enhancing effect, such as a layer composed of a fluorine-free (meth)acrylate resin, is not formed on the surface of the low refractive index layer 16. By not providing such a primer layer, the structure of the anti-reflection film 20 is simplified, and the productivity and cost suppression effect of the anti-reflection film 20 are improved.

[0119] <Other types of anti-reflection films>

[0120] As described above, the anti-reflection film according to the present invention is formed by stacking a hard coating layer 14 and a low refractive index layer 16 in order on the surface of a base film 12, and further stacking an antifouling layer 18 as desired, and the low refractive index layer 16 has a predetermined composition, and is not limited to the anti-reflection film 10 according to the first embodiment or the anti-reflection film 20 according to the second embodiment. Other embodiments of the anti-reflection film according to the present invention are exemplified below.

[0121] (Third Embodiment)

[0122] Figure 3 3 shows an anti-reflection film 30 according to the third embodiment. The anti-reflection film 30 according to the third embodiment includes: a base film 12; a hard coating layer 14 formed on the surface of the base film 12; a high refractive index layer 15 formed on the surface of the hard coating layer 14; and a low refractive index layer 16 formed on the surface of the high refractive index layer 15.

[0123] The antireflection film 30 according to the third embodiment is different from the antireflection film 10 according to the first embodiment in that a high refractive index layer 15 is provided between the hard coat layer 14 and the low refractive index layer 16. Other than this, it is the same as the antireflection film 10 according to the first embodiment, and the description of the same configuration is omitted.

[0124] The high refractive index layer 15 is a layer having a higher refractive index than the hard coating layer 14 and the low refractive index layer 16. By arranging the high refractive index layer 15 between the hard coating layer 14 and the low refractive index layer 16, the anti-reflection film 30 exhibits a high anti-reflection effect. The refractive index of the high refractive index layer 15 is preferably within the range of 1.55 or more and 1.80 or less. More preferably, it is 1.60 or more, and furthermore, it is 1.70 or less.

[0125] The constituent material of the high refractive index layer 15 is not particularly limited, as long as the known material used for anti-reflection film etc. in the past can be used in a manner that can obtain a predetermined refractive index. For example, as a material that can be used in the hard coat layer 14 or the low refractive index 16, it is only necessary to appropriately select from the materials described above. The refractive index of the high refractive index layer 15 can be adjusted by the type and mixing amount of the binder resin, inorganic oxide particles, and resin particles. For example, by adding inorganic oxide particles in a sufficient amount, a high refractive index layer 15 having a refractive index higher than that of the low refractive index layer 16 can be formed.

[0126] The average thickness of the high refractive index layer 15 varies depending on the setting of the refractive index, but by setting it to 50 nm to 200 nm, for example, the antireflection function can be further improved. The high refractive index layer 15 may be formed by laminating two or more layers having different refractive indices.

[0127] (Fourth Embodiment)

[0128] Figure 4 4 shows an anti-reflection film 40 according to a fourth embodiment. The anti-reflection film 40 according to the fourth embodiment includes: a base film 12; a hard coating layer 14 formed on one surface of the base film 12; and a low refractive index layer 16 formed on the surface of the hard coating layer 14. In addition, a transparent adhesive layer 22 is provided on the other surface of the base film 12. A release film 24 is provided on the surface of the transparent adhesive layer 22 as required. The release film 24 functions as a protective layer of the transparent adhesive layer 22 before the anti-reflection film 40 is used, and is peeled off from the transparent adhesive layer 22 when the anti-reflection film 40 is used.

[0129] The anti-reflection film 40 involved in the fourth embodiment is different from the anti-reflection film 10 involved in the first embodiment in that it has a transparent adhesive layer 22 on the other side of the base film 12. Otherwise, it is the same as the anti-reflection film 10 involved in the first embodiment, and the description of the same structure is omitted.

[0130] The transparent adhesive layer 22 is used to adhere the anti-reflection film 40 to the surface of a display or the like with good adhesion. In addition, the anti-reflection film 40 has the effect of preventing the glass of the display or the like from scattering by having the transparent adhesive layer 22. That is, the anti-reflection film 40 also functions as an anti-scattering film.

[0131] The adhesive composition forming the transparent adhesive layer 22 can contain known adhesive resins such as acrylic adhesives, silicone adhesives, and urethane adhesives. Among them, acrylic adhesives are preferred from the viewpoint of optical transparency or heat resistance. In order to improve the cohesive force of the transparent adhesive layer 22, it is preferred that the adhesive composition contains a crosslinking agent. As the crosslinking agent, isocyanate crosslinking agents, epoxy crosslinking agents, aziridine crosslinking agents, chelate crosslinking agents, etc. can be listed.

[0132] Adhesive composition can also include additives as required. As additives, known additives such as plasticizers, silane coupling agents, surfactants, antioxidants, fillers, curing accelerators, and curing retardants can be listed. In addition, from the viewpoints such as productivity, organic solvents can also be used for dilution.

[0133] The thickness of the transparent adhesive layer 22 is not particularly limited, but is preferably within a range of 5 μm or more and 100 μm or less, and more preferably 10 μm or more and 50 μm or less.

[0134] The transparent adhesive layer 22 can be formed by the following methods, etc.: a method of directly applying an adhesive composition on the other side of the substrate film 12 to form a transparent adhesive layer; a method of applying an adhesive composition on the surface of a release film 24 to form a transparent adhesive layer and then transferring the transparent adhesive layer to the other side of the substrate film 12; and a method of applying an adhesive composition on the surface of a first release film to form a transparent adhesive layer, then laminating a second release film, peeling off either release film and transferring the transparent adhesive layer to the other side of the substrate film 12.

[0135] From the viewpoint of the effect of preventing glass scattering, the adhesive force of the transparent adhesive layer 22 to the glass is preferably 4 N / 25 mm or more, more preferably 6 N / 25 mm or more, and even more preferably 10 N / 25 mm or more.

[0136] (Fifth Embodiment)

[0137] Figure 52 shows an anti-reflection film 50 according to the fifth embodiment. The anti-reflection film 50 according to the fifth embodiment includes: a base film 12; a hard coating layer 14 formed on one surface of the base film 12; a low refractive index layer 16 formed on the surface of the hard coating layer 14; and a protective film 28 disposed on the surface of the low refractive index layer 16 via an adhesive layer 26. In addition, a transparent adhesive layer 22 is provided on the other surface of the base film 12. A release film 24 is disposed on the surface of the transparent adhesive layer 22 as required.

[0138] The anti-reflection film 50 involved in the fifth embodiment is different from the anti-reflection film 40 involved in the fourth embodiment in that a protective film 28 is provided on the surface of the low refractive index layer 16 via an adhesive layer 26. Other than this, it is the same as the anti-reflection film 40 involved in the fourth embodiment, and the description of the same structure is omitted.

[0139] The protective film 28 can prevent the surface of the low refractive index layer 16 from being damaged when the protective film 28 is continuously processed by a rolling process or attached to the anti-reflection film 50 such as a display. The protective film 28 is attached to the surface of the low refractive index layer 16 via the adhesive layer 26. The protective film 28 is peeled off from the surface of the low refractive index layer 16 together with the adhesive layer 26 after the processing of the anti-reflection film 50. Therefore, with respect to the adhesive layer 26, the adhesive force between the protective film 28 and the adhesive layer 26 is stronger than the adhesive force between the low refractive index layer 16 and the adhesive layer 26, and the adhesive force is adjusted to a degree that the interface between the low refractive index layer 16 and the adhesive layer 26 can be peeled off. In the anti-reflection film 50 involved in this embodiment, the water contact angle of the surface is defined relative to the surface in a state after the protective film 28 and the adhesive layer 26 are peeled off, and the water contact angle of the surface after they are peeled off is 100° or more.

[0140] The material constituting the protective film 28 can be appropriately selected from the materials exemplified as the material constituting the base film 12. The thickness of the protective film 28 is not particularly limited, but can be set within the range of 2 μm to 500 μm or within the range of 2 μm to 200 μm.

[0141] As the adhesive layer 26, the adhesive layer described in Patent Document 1 can be suitably applied. The adhesive forming the adhesive layer 26 is not particularly limited, and acrylic adhesives, silicone adhesives, urethane adhesives, etc. can be suitably used. In particular, acrylic adhesives are suitable because of their excellent transparency or heat resistance. Preferably, the acrylic adhesive is formed from an adhesive composition containing a (meth)acrylic polymer and a crosslinking agent.

[0142] The (meth)acrylic polymer is a homopolymer or copolymer of a (meth)acrylic monomer. Examples of the (meth)acrylic monomer include an alkyl group-containing (meth)acrylic monomer, a carboxyl group-containing (meth)acrylic monomer, and a hydroxyl group-containing (meth)acrylic monomer.

[0143] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, metal chelate crosslinking agents, metal alkoxide crosslinking agents, carbodiimide crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, and melamine crosslinking agents. The crosslinking agent may be used alone or in combination of two or more.

[0144] The adhesive composition may also include other additives in addition to the (meth) acrylic polymer and the crosslinking agent. Other additives include crosslinking accelerators, crosslinking delay agents, resins (tackifiers) that impart adhesiveness, antistatic agents, silane coupling agents, plasticizers, stripping aids, pigments, dyes, wetting agents, thickeners, ultraviolet light absorbers, preservatives, antioxidants, metal deactivators, alkylating agents, flame retardants, etc. These additives are appropriately selected for use according to the purpose or use purpose of the adhesive.

[0145] The thickness of the adhesive layer 26 is not particularly limited, but is preferably within a range of 1 μm or more and 10 μm or less, and more preferably 2 μm or more and 7 μm or less.

[0146] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment at all, and various changes can be made within the scope not departing from the gist of the present invention.

[0147] For example, in the above-mentioned embodiment, it is described that the surface of the base film 12 can be subjected to a surface treatment. However, instead of the surface treatment, an easy-adhesion layer may be provided on the surface of the base film 12 .

[0148] like Figure 3 As shown, the high refractive index layer 15 in the third embodiment is added to Figure 1 The antireflection film 10 of the first embodiment is shown in the form of a film, but it may also be added to Figure 2 The anti-reflection film 20 of the second embodiment is shown in FIG. Figure 4 As shown, the transparent adhesive layer 22 and the release film 24 in the fourth embodiment are added to Figure 1 The antireflection film 10 of the first embodiment is shown in the form of a film, but it may also be added to Figure 2 The antireflection film 20 of the second embodiment shown or Figure 3 The anti-reflection film 30 of the third embodiment is shown in FIG. Figure 5As shown, the adhesive layer 26 and the protective film 28 in the fifth embodiment are added to Figure 4 The anti-reflection film 40 of the fourth embodiment is shown in the form of a film, but it can also be added to Figure 1 The antireflection film 10 of the first embodiment shown or Figure 2 The anti-reflection film 20 of the second embodiment shown in the figure may also be added to Figure 3 The form of the anti-reflection film 30 of the third embodiment is shown. When the adhesive layer 26 and the protective film 28 are added to the anti-reflection film 20 of the second embodiment, the adhesive layer 26 has a stronger adhesive force between the protective film 28 and the adhesive layer 26 than the adhesive force between the anti-fouling layer 18 and the adhesive layer 26, and the adhesive force is adjusted to a degree that the interface between the anti-fouling layer 18 and the adhesive layer 26 can be peeled off.

[0149] Furthermore, before forming each layer, various functional layers such as a gas barrier improving layer, an antistatic layer, and an oligomer block layer may be provided on the surface of the base film 12. As the antistatic layer, the antistatic layer described in Patent Document 1 can be suitably applied.

[0150] Example

[0151] Hereinafter, the present invention will be described in detail using Examples and Comparative Examples. Unless otherwise specified, the preparation and evaluation of samples were performed at room temperature in the atmosphere.

[0152] <Preparation of hard coat layer forming composition>

[0153] A photopolymerization initiator "Omnirad 127" (manufactured by IGM Resins BV) was added to an ultraviolet curable resin composition ESS-620 (manufactured by DIC, urethane acrylate resin, solvent (ethyl acetate), solid content concentration 79% by mass) so as to be 3% by mass relative to the total solid content of the hard coat layer forming composition. Furthermore, ethyl acetate was added so that the solid content concentration became 31% by mass to prepare a hard coat layer forming composition.

[0154] <Preparation of high refractive index layer-forming composition>

[0155] Methyl ethyl ketone was added to an ultraviolet curable resin composition TYZ65-01 (manufactured by Toyochem, acrylic resin, zirconium oxide (average particle size 80 nm), a photopolymerization initiator (the above-mentioned "Omnirad127"), a solvent (cyclohexanone, methyl isobutyl ketone, propylene glycol monomethyl ether), and a solid content concentration of 35% by mass) to make the solid content concentration become 8% by mass, to prepare a composition for forming a high refractive index layer.

[0156] <Preparation of alumina particles surface-treated with a silane coupling agent having a reactive group>

[0157] Into a 500 ml stainless steel can, 25 g of unsurface-treated alumina particles (average particle size 160 nm), 2.5 g of a silane coupling agent ("KBM-5103" manufactured by Shin-Etsu Chemical Co., Ltd., 3-acryloxypropyltrimethoxysilane), and 72.5 g of propylene glycol monomethyl ether were added, and mixed and dispersed at 4000 rpm for 30 minutes using a homomixer ("Homomixer MARKII 2.5" manufactured by Primex Corporation), to obtain a dispersion 1 of alumina particles surface-treated by a silane coupling agent having an acryl group as a reactive group.

[0158] <Preparation of Composition for Forming Low Refractive Index Layer>

[0159] A binder resin, hollow silica particles, alumina particles, fluorine-containing (meth)acrylate (only Example 2 and Comparative Example 2) and a photopolymerization initiator were mixed in a manner to obtain the mixed composition (mass % of all solid contents) described in Table 1, and the solid content concentration was adjusted to the concentration described in Table 1 using a solvent (MEK / PGM=1 / 3) to prepare a composition for forming a low refractive index layer.

[0160] The materials used as the material of the low refractive index layer forming composition are as follows.

[0161] · Binder resin: "Aronix MT-3041" manufactured by Toagosei Co., Ltd., multifunctional acrylate, solid content concentration 100% by mass

[0162] Hollow silica particles: "THRULYA4320" manufactured by JGC Catalysts & Chemicals, average particle size 60 nm, solvent: MIBK, solid content concentration 20% by mass

[0163] Alumina particles 1: the above-mentioned alumina particles dispersion 1

[0164] Alumina particles 2: Alumina sol "LIODURAS KT-110AL" manufactured by Toyochem; 25% by mass of alumina particles (average particle size: 110 nm, no surface treatment), 15% by mass of photosensitive monomer and resin, solvent (MEK, cyclohexanone, aliphatic solvent)

[0165] Fluorinated (meth)acrylate: "KY-1216" manufactured by Shin-Etsu Chemical Co., Ltd., perfluoropolyether-containing (meth)acrylate, methyl ethyl ketone; solid content concentration 20% by mass

[0166] · Photopolymerization initiator: the above-mentioned "Omnirad127"

[0167] <Preparation of antifouling layer-forming composition>

[0168] A fluorine-containing compound (the above-mentioned "KY-1216") and a photopolymerization initiator (the above-mentioned "Omnirad127") were mixed in a manner to obtain a mixed composition (mass % of all solid components) as described in Table 1, and the solid content concentration was adjusted to the concentration described in Table 1 using a solvent (MEK / PGM=1 / 3) to prepare a composition for forming an antifouling layer.

[0169] <Production of hard coating>

[0170] For each of Examples 1 to 2 and Comparative Examples 1 to 3, the hard coat layer-forming composition was applied on a substrate film ("Lumirror #50-U403" manufactured by TORAY, a polyethylene terephthalate film, 50 μm thick) using a #12 wire bar, dried at 80° C. for 60 seconds, and then irradiated with a high-pressure mercury lamp at a light intensity of 200 mJ / cm 2 The ultraviolet rays formed a hard coating (film thickness 4μm).

[0171] <Production of high refractive index layer>

[0172] For each of Examples 1 to 2 and Comparative Examples 1 to 3, a high refractive index layer-forming composition was applied on the surface of the hard coat layer, dried at 80° C. for 60 seconds, and then irradiated with a high pressure mercury lamp at a light intensity of 200 mJ / cm in a nitrogen atmosphere. 2 Ultraviolet rays form a high refractive index layer (film thickness 110nm).

[0173] <Production of low refractive index layer>

[0174] For each of Examples 1 to 2 and Comparative Examples 1 to 3, a low refractive index layer-forming composition was applied onto the surface of the high refractive index layer using a #3 wire bar, dried at 100° C. for 60 seconds, and then irradiated with a high-pressure mercury lamp at a light intensity of 200 mJ / cm in a nitrogen atmosphere. 2 The ultraviolet rays form a low refractive index layer. The film thickness is shown in Table 1.

[0175] <Production of antifouling layer>

[0176] In Example 1 and Comparative Example 1, the antifouling layer-forming composition was applied to the surface of the low refractive index layer using a #3 wire rod, dried at 100° C. for 60 seconds, and then irradiated with a high-pressure mercury lamp at a light intensity of 200 mJ / cm in a nitrogen atmosphere. 2 The film thickness is shown in Table 1. No antifouling layer was formed in Example 2 and Comparative Examples 2 to 3.

[0177] Based on the above, antireflection films according to Examples 1 and 2 and Comparative Examples 1 to 3 were produced.

[0178] <Evaluation Method>

[0179] (Thickness and refractive index of each layer)

[0180] For each sample, the thickness and refractive index of the hard coating layer, high refractive index layer, low refractive index layer, and antifouling layer were evaluated. At this time, each time each layer was formed, the reflection spectrum in the wavelength region of 380 to 780 nm obtained using a microscopic spectrophotometer ("OPTM-F1" manufactured by Otsuka Electronics) and the theoretical spectrum derived based on the Fresnel formula were curve-fitted by the least squares method to calculate the thickness of each layer and the refractive index at a wavelength of 589.3 nm.

[0181] (Visual reflectivity)

[0182] The back side of the anti-reflection film (the side opposite to the low refractive index layer) was roughened with #400 sandpaper, and black paint was applied to the entire surface. The 5° regular reflectance of the surface of the anti-reflection film at a wavelength of 380nm to 780nm was measured using an ultraviolet visible near-infrared spectrophotometer ("UV-3600" manufactured by Shimadzu Corporation), and the visual reflectance was calculated by multiplying the measured value by the visual sensitivity value. If the visual reflectance is 2.0% or less, it can be considered that the anti-reflection property is sufficient.

[0183] (Water contact angle)

[0184] The surface of the produced antireflection film was measured for water contact angle. In the measurement, 4 μL of pure water was dripped onto the surface of the sample (the surface of the antifouling layer for Example 1 and Comparative Example 1, and the surface of the low refractive index layer for Example 2 and Comparative Examples 2 to 3) using a contact angle meter (DropMaster DMo-502 manufactured by Kyowa Interface Science) to measure the water contact angle. If the water contact angle is 100° or more, it can be considered to be sufficiently large from the perspective of antifouling properties.

[0185] (Wear durability)

[0186] The wear durability of each sample was evaluated by an eraser wear test using the water contact angle as an index.

[0187] Each sample has been subjected to the eraser wear test.At this point, use the plane wear tester (" DAS-400 " manufactured by Daiei Scientific Precision Machinery Manufacturing Institute), the eraser wear test is placed on the surface of the anti-reflection film of each sample with an eraser (manufactured by Minoan Company, the contact surface is a cylindrical type with a diameter of φ 6mm) and it is reciprocated.The stroke length of the test bench is made into 50mm, the test bench reciprocating speed is made into 30 reciprocating / minute, and the applied load is made into 1.0kg.Till 500 reciprocating, the water contact angle is measured by every 100 reciprocating, when exceeding 500 reciprocating, the water contact angle is measured by every 500 reciprocating afterwards, the maximum reciprocating number of times of the water contact angle above 90 ° is kept as an evaluation value.If the evaluation value is more than 2000 times, it can be considered to have enough wear durability.And, if the evaluation value is more than 4000 times, it can be considered to have high wear durability. The water contact angle was measured by dropping 4 μL of pure water on the surface of the antireflection film using a contact angle meter (DropMaster DMo-502 manufactured by Kyowa Interface Science Co., Ltd.).

[0188] (Solvent resistance)

[0189] Each sample was subjected to an eraser abrasion test in the presence of ethanol, and solvent resistance using water contact angle as an index was evaluated.

[0190] Each sample has been subjected to the eraser wear test.At this moment, use plane wear tester (" DAS-400 " manufactured by Daiei Scientific Precision Machinery Manufacturing Institute), eraser (Minoan company manufactures, contact surface is the cylindrical type of diameter φ 6mm) is placed on the surface of the anti-reflection film of each sample and make it go back and forth 1500 times with eraser of eraser wear test.The stroke length of test bench is made as 50mm, and the test bench reciprocating speed is made as 30 reciprocating / minute, and the applied load is made as 1.0kg.At this moment, before the test starts and when every 200 reciprocating, use micropipette to drip 200 μ L of ethanol to the position that the eraser of each sample contacts.After 1500 reciprocating, measure contact angle, if drop to less than 90 °, then be evaluated as solvent resistance low (×).On the other hand, if maintain the water contact angle more than 90 °, then be evaluated as solvent resistance high (○). In addition, when the water contact angle of 90° or more is maintained and no wear marks (changes in the reflection characteristics of the friction site) are observed, it is considered that the solvent resistance is particularly excellent (⊚).

[0191] (Abrasion resistance)

[0192] Each sample was subjected to a steel wool resistance test. At this time, a flat wear tester ("DAS-400" manufactured by Daiei Kagaku Seiki Co., Ltd.) was used to place steel wool #0000 (manufactured by Nippon Steel Wool Co., Ltd.) fixed on a 20mm×20mm flat friction piece on the surface of the anti-reflection film of each sample and make it reciprocate. The stroke length of the test bench was set to 50mm, the reciprocating speed of the test bench was set to 60 reciprocating times / minute, the applied load was set to 1.5kg, and it was moved back and forth 100 times. The sample with a scratch of more than 10mm in length on the anti-reflection film after the test was evaluated as having low scratch resistance (×). In addition, the sample with a scratch of less than 10mm in length but no scratch of more than 10mm in length was evaluated as having high scratch resistance (○). This degree of scratches will not cause problems in practical use. Moreover, the sample without scratches was evaluated as having very high scratch resistance (◎).

[0193] <Evaluation Results>

[0194] Table 1 shows the evaluation results of Examples 1 to 2 and Comparative Examples 1 to 3 together with the component compositions of the low refractive index layer and the antifouling layer (unit: mass % of the total solid content of each layer) and the layer configuration of the antireflection film.

[0195] [Table 1]

[0196]

[0197] As shown in Table 1, in Examples 1 to 2, the water contact angle on the surface of the anti-reflection film is more than 100°, indicating that the anti-reflection film has high antifouling properties. In addition, in Examples 1 to 2, high wear durability with an evaluation value of more than 2,000 times and high solvent resistance evaluated as "◎" or "○" were obtained. At the same time, it has a high scratch resistance evaluated as "◎". This is believed to be because the composition constituting the low refractive index layer contains, in addition to the (meth)acrylate compound having a reactive group and hollow silica particles, aluminum oxide particles surface-treated by a silane coupling agent having a reactive group that can form a bond with the (meth)acrylate compound.

[0198] Among them, in Example 1, particularly high solvent resistance evaluated as "◎" was obtained corresponding to the presence of an antifouling layer composed of a cured product of a composition containing a fluorine-containing (meth)acrylate on the surface of the low refractive index layer.

[0199] On the other hand, Comparative Examples 1 and 2 are compared with Examples 1 and 2 respectively, and the difference is that the aluminum oxide particles contained in the low refractive index layer are not aluminum oxide particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with a (meth)acrylate compound. Correspondingly, the wear durability and solvent resistance are reduced. The scratch resistance is also reduced compared with Examples 1 and 2.

[0200] In Comparative Example 3, the water contact angle of the antireflection film surface was less than 100°, indicating that the antireflection film had low antifouling properties. Abrasion durability, solvent resistance, and scratch resistance were also insufficient.

[0201] As described above, since the antireflection film is an antireflection film having a substrate film, a hard coating layer formed on the surface of the substrate film, and a low refractive index layer formed on the surface of the hard coating layer, or further having an antifouling layer formed on the surface of the low refractive index layer, the low refractive index layer is composed of a cured product of an ionizing radiation curable composition containing a (meth) acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth) acrylate compound, the water contact angle of the antireflection film surface is 100° or more, so that the antireflection film has excellent antifouling properties and scratch resistance, and has high wear durability and solvent resistance. It can also withstand friction by a cloth or finger with a solvent such as alcohol attached.

[0202] Although the embodiments of the present invention have been described above, the present invention is not limited to the above embodiments at all, and various modifications can be made without departing from the gist of the present invention.

[0203] Description of Reference Numerals

[0204] 10, 20, 30, 40, 50 anti-reflection film

[0205] 12 Base film

[0206] 14Hard coating

[0207] 15 High refractive index layer

[0208] 16 Low refractive index layer

[0209] 18 Antifouling layer

[0210] 22 transparent adhesive layer

[0211] 24 Release film

[0212] 26 Adhesive layer

[0213] 28 protective film.

Claims

1. An antireflection film comprising a base film, a hard coating layer formed on a surface of the base film, and a low refractive index layer formed on a surface of the hard coating layer, characterized in that: The low refractive index layer is composed of a cured product of an ionizing radiation curable composition, wherein the ionizing radiation curable composition contains a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound. The water contact angle of the surface of the antireflection film is 100° or more.

2. The antireflection film according to claim 1, wherein The ionizing radiation curable composition constituting the low refractive index layer further contains a fluorine-containing (meth)acrylate.

3. An antireflection film comprising a substrate film, a hard coating layer formed on a surface of the substrate film, a low refractive index layer formed on a surface of the hard coating layer, and an antifouling layer formed on a surface of the low refractive index layer, characterized in that: The low refractive index layer is composed of a cured product of an ionizing radiation curable composition, wherein the ionizing radiation curable composition contains a (meth)acrylate compound having a reactive group, hollow silica particles, and alumina particles surface-treated with a silane coupling agent having a reactive group capable of forming a bond with the (meth)acrylate compound. The antifouling layer is composed of a cured product of an ionizing radiation curable composition containing a fluorine-containing (meth)acrylate. The water contact angle of the surface of the antireflection film is 100° or more.

4. The antireflection film according to claim 3, wherein: The content of the fluorine-containing (meth)acrylate in the antifouling layer is 90% by mass or more based on the total solid content of the antifouling layer.

5. The antireflection film according to claim 3 or 4, wherein: The low refractive index layer does not contain a fluorine-containing compound.

Citation Information

Patent Citations

  • Anti-reflection film

    WO2021020504A1